Cuminum Cyminum L Encapsulation on Perlite/calcium alginate/single walled carbon nanotubes -Glucose Composite: Fabrication, Characterization, Antibacterial and Antifungal Properties - Mahdieh Chegeni; Mozhgan Mehri; Zahra Shokri Rozbahani (Nanochemistry Research)
This study presents the preparation and application of a perlite/calcium alginate/single walled carbon nanotubes-Glucose composite for the cumin encapsulation as an essential oil using a simple method. The as-prepared composite was analyzed using Fourier transformed infrared (FTIR), field emission scanning electron microscopy (FESEM), X-ray diffractometer (XRD), dynamic light scattering (DLS), and thermo gravimetric analysis (TGA). The effect of important factors was determined by evaluating pH, cumin concentration, perlite/calcium alginate/single walled carbon nanotubes-Glucose dosage, and time. Based on the data, the high percentage of cumin encapsulation was achieved at low pH. The release profile of cumin was studied at pH=7, and the maximum release was obtained after 48 h. The antibacterial and antifungal properties of cumin-loaded perlite/calcium alginate/single walled carbon nanotubes -Glucose were also evaluated against Candida albicans, Gram negative (Escherichia coli) and Gram positive (Staphylococcus aureus) bacteria, which represented more photogenic detection compared to that of cumin. Finally, this work demonstrates the efficient application of perlite/calcium alginate/single walled carbon nanotubes-Glucose for the encapsulation of cumin and pathogen detection.